Report of the Study Team on Tribal Development Programmes Madhya Pradesh - Planning Commission (Planning Commission, 1966)
Madhya Pradesh, the largest of all States in India, lies between 18.0° and 26.5° North latitude and 74.0° and 84.5°, East longitude. Situated in the Central region of India it is surrounded by the State of Uttar Pradesh on the north, the States of Bihar and Orissa on the east, Andhra Pradesh and Maharashtra on the south and Gujarat and Rajasthan on the west. Administratively, the State is divided into seven divisions and 43 districts.
Committee on Plan Projects, Planning Commission